Experimental investigation of extreme wave impacts on a rigid TLP model in cyclonic conditions. (17th February 2017) - Abdussamie, Nagi; Ojeda, Roberto; Drobyshevski, Yuriy; Thomas, Giles; Amin, Walid
Abstract : This paper describes a series of model tests of a rigidly mounted tension leg platform (TLP) subjected to extreme wave events corresponding to long-crested irregular wave trains of a 10, 000-year cyclonic sea state. The experimental setup was instrumented to simultaneously measure wave surface elevations in the vicinity of the model, global wave impact forces and local pressure distribution on the underside of the model's topside deck. Model accelerations were also monitored for each wave impact event so that the inertial force due to structural dynamic response could be identified. The deck–column intersection areas were found to experience large wave-in-deck slamming pressures, in particular around the aft columns. A reduction of the deck clearance was found to increase the magnitude of the global horizontal forces; however, the global vertical forces and local wave-in-deck slamming pressures did not follow this trend.